The role of multiple interfaces induced by hierarchical phase structures in the corrosion of low-cost titanium alloys - Zhongli Qiao; Qinyang Zhao; Ping Guo; Cheng Lin; Huan Wang; Runqi Zhang; Zixuan Meng; Kuaishe Wang; Yongqing Zhao (Materials & Design)
Recently, there has been a growing anticipation for developing titanium alloys with low cost and excellent properties. Working towards this goal, a hierarchical phase structure comprising micron-scale α phase and micron-scale and nano-scale α′ phases in Ti-Al-V-Fe-Mo alloys was obtained via vacuum melting, forging, and solution treatment. The high-density hierarchical α′ martensite in Ti-Al-V-Fe-Mo alloys exhibits the high grain boundary density and the weak segregation of Fe and Mo. It promotes the formation of passivation films with low defect density and high film resistance on the alloy surface and the homogenous distribution of solutes within the matrix. This homogeneity significantly diminishes the tendency for pitting corrosion and enhances the overall corrosion resistance of the alloys. In addition, the analysed results of the valence electron theory model show the high electron density difference at α(0001)//β(110) is the primary reason for pitting in the interface of α/β. And the low strongest-bond energy of the α phase leads to its preferential corroded. The calculated results provide theoretical support for the experimental phenomena.